Modern Christian thought The twentieth century - Livingston, James C.; Francis Schussler Fiorenza; Sarah Cokley; James H. Evans, Jr (Upper Saddle River Prentice Hall, 1997)
This extensive book bestows readers with full expositions of the thought of the leading modern theologians and philosophers of religion since the eighteenth century Enlightenment.
Keywords: Theology, Doctrinal -- History -- Modern period, 1500- Theology, Doctrinal -- Modern period